Sustainable Fisheries Management through Certification, Conservation-Based Economic (Study Case: Pangkep Regency) - Safitri, Dian Rachma; Budiman, Irham (Journal of Indonesian Coral Reefs, 2012)
The purpose of this paper is to analyze the efforts of increasing conservation-based fishery management by applying a certification system and providing recommended formula of strategic policy in the continuing fishery certification system. Nowadays, the degradation rate of coastal and marine resources is so quickly with a very high damage level. Along with the worldÃ¢â¬â¢s fishery policy which refers to the Code of Conduct for Responsible Fisheries, there are some obligations from fish producer countries to apply the use of fish and reef resources more environmental-friendly, one of them is by doing the certification towards the environmental management and fishing techniques. Ecolabel certification is a certification system to indicate that the certificated product was produced by following principles of environmental preservation and sustainable process. Thus, the certifier can help consumer to distinguish between certified product or non-certified product. The ecolabel certification are based on three main concepts: the natural resources for sustainable production, ecological, and sosio-cultural. Indonesia must apply the fishery certification system because the damage level of coastal and marine ecosystems in Indonesia is very high. This paper explains the effectiveness of marine ornamental fish certification that has been conducted in Pangkep Regency, Indonesia. The program was conducted by a local certification department, International Certification Quality, in collaboration with COREMAP by using adopted standard of Marine Aquarium Council (MAC).